Feasibility Analysis of Indonesian Language Textbooks for High School Class XII Curriculum 2013 Issued by the Ministry of Education and Culture 2015 - Rika Afriana; Regita Firjiantia; Resi Afuri; Restiani; Riska Putri Dinita; Muhammad Mukhlis (UIR Press, 2022)
Teachers still complain about Indonesian language textbooks in the second semester of the twelfth semester because there are still many shortcomings in language and content. The purpose of this study was to describe and analyze the feasibility of the second semester of the twelfth semester of Indonesian language textbooks used by SMA Islam Sudirman. Aspects of the feasibility of the assessment are language and content. The data collection in this qualitative research uses the listening and proficient method, while the content analysis method is used to analyze the data. This study uses the expert triangulation method to test the validity of the data, namely researchers, teachers and students filling in the data generated by the data card based on the feasibility of the text book. The results of this study indicate the feasibility of textbooks in terms of language and content. The language and content scores are 56.3 and 51.9, so they are still not feasible. Both aspects need to be improved so that this textbook is suitable for both teachers and students.